Kickboxing review: anthropometric, psychophysiological and activity profiles and injury epidemiology - M Slimani; H Chaabene; B Miarka; E Franchini; K Chamari; F Cheour (Termedia Publishing House, 2017)
Kickboxing is one of the modern combat sports. The psychophysiological demands of a kickboxing competition require athletes to achieve high thresholds of several aspects of physical fitness. The aim of the current review is to critically analyse and appraise the kickboxer's anthropometric, physiological, physical and psychological attributes with the activity profile and injury epidemiology in order to provide practical recommendations for training as well as new areas of scientific research. The available information shows that both amateur and elite-level male kickboxers are characterized by a higher proportion of mesomorphy with a well-developed muscle mass and low body fat percentage. While there is some variation in the maximum oxygen uptake of kickboxers, moderate to high cardio-respiratory levels are reported for these athletes. Regardless of kickboxers' level, a high peak and mean anaerobic power output were reported. High-level kickboxing performance also requires well-developed muscle power in both the upper and lower limbs. Psychological factors contribute to success that requires high levels of self-confidence, motivation, dispositional hope and optimism, mental toughness/resiliency, and adaptive perfectionism. Psychological attributes also distinguished successful from less successful kickboxers. The activity-to-rest ratio was higher in elite (1:1) than both amateur and national-level (from 1:2 to 1:5) kickboxers, with no significant differences between rounds (round 1=1:4, and rounds 2 and 3=1:5) as well as between winners and losers in amateur and national-level simulated combats. These particular psychophysiological characteristics and performance aspects of kickboxers influence performance and could serve as guidance for training. Finally, kickboxing is characterized by chronic repetitive head trauma, which causes hypopituitarism due to traumatic brain injury (TBI). Future investigations into the physical, physiological and psychological characteristics related to age, gender and competitive levels of kickboxers are required to enrich the current knowledge and to help create the most suitable training programme.